Ultralight biomedical TC4-Cu alloy achieveing superior mechanical properties and osseointegration - Zonghao Li; Xuanyi Shen; Hongyan Hu; Chengguo Mei; Zhitong Kui; Zhengyuan He; Zhenhua Li; Yehua Jiang (Materials & Design)
Balancing high strength and low modulus in porous Cu-bearing Ti alloy remains challenging. Here, honeycomb-structured porous TC4-5Cu alloys (pore size: 500 ∼ 800 μm, lateral through pores: 250 μm) are fabricated via laser powder bed fusion to overcome this challenge, and their microstructure, mechanical properties and in vivo biocompatibility are evaluated. The alloys consist of α' /α, β, and Ti2Cu phases, with α' /α diffraction intensity decreasing as pore size increases. Along the build direction, nanotwinned α'  and nanospherical Ti2Cu phases are identified in the 700 μm alloy. As the pore size increases to 800 μm, more nanotwinned α'  and refined nanospherical Ti2Cu phases are observed. The alloys exhibit low density (2.93 ∼ 2.34 g/cm3), low modulus (38.9 ∼ 31.2 GPa)and high yield strength (1106.1 ∼ 751.3 MPa), with all properties decreasing with increasing pore size. Notably, the alloy with a pore size of 800 μm displays strength similar to that of the 700 μm alloy, due to strengthening induced by nanotwinned α'  and nanospherical Ti2Cu phases. When implanted in rabbits for 4 ∼ 12 weeks, porous TC4-5Cu alloys exhibit superior osseointegration and lower inflammatory factors than commercial TC4 implants, demonstrating great potential for orthopedic applications.